EFFECT OF OSTERIX AND OSTEOCALCIN ENHANCEMENT BY QUERCETIN (3,3′,4′,5,7-PENTAHYDROXYFLAVONE) ON OSTEOBLAST HFOB 1.19 CELL LINE - ADITAMA, AGNIS PONDINEKA RIA; MA’ARIF, BURHAN; MUSLIKH, FAISAL AKHMAL (International Journal of Applied Pharmaceutics, 2022)
Objective: This study was aimed at investigating the effect of quercetin (3,3′,4′,5,7-pentahydroxyflavone) as a phytoestrogen in the treatment of estrogen deficiency-induced osteoporosis, through the measurement of osterix and osteocalcin expressions on osteoblast hFOB 1.19 cell line. Methods: hFOB 1.19 cells were cultured in 24-well microplates, induced with 10 ng/ml TNF-α and incubated for 24 h. TNF-α induction was used to create an estrogen deficiency condition. Quercetin was then added at 10 µM concentration. The immunocytochemistry double staining method was performed with anti-rabbit osterix primary antibody and anti-mouse osteocalcin primary antibody. The cells were then incubated at 4 °C overnight. Finally, an anti-rabbit secondary antibody FITC and anti-mouse secondary antibody rhodamine were added before the cells were analyzed using a Confocal Instrument Laser Scanning Microscopy (CLSM) at 488 and 543 nm. Results: Quercetin increased the expressions of both osterix and osteocalcin in the osteoblast hFOB 1.19 cell line compared to the negative controls (p<0.005), with expression values of 57852*±3878.71 AU and 24161.75*±1498.65 AU, respectively. Conclusion: Quercetin shows an anti-osteoporosis effect by increasing the expressions of both osterix and osteocalcin in osteoblast hFOB 1.19 cell line.